Burden of Mortality and Morbidity in the Colombian Population aged 15 to 49 Years: an Epidemiological Analysis of two Decades - Brian Johan Bustos Viviescas; Carlos Enrique García Yerena; Amalia Villamizar Navarro (Revista Finlay, 2025)
Foundation: epidemiological analysis of the mortality and morbidity burden in Colombians aged 15 to 49 years over the last two decades (1999-2019) reveals significant data on the health of the Colombian population. Objective: to identify detailed data on the causes of mortality and morbidity in the 15- to 49-year-old segment to demonstrate the impact of diseases and risk factors that impact the well-being of the population. Method: in the present study, the mortality and morbidity burden in Colombians aged 15 to 49 years was analyzed over two decades (1999-2009; 2009-2019). These data are publicly available and were collected considering the variables of year, age, and sex. Results: women have higher mortality from non-communicable diseases such as neoplasms, and men from suicide and interpersonal violence, results that remained consistent across decades. A high likelihood of multicomorbidity was evident when considering the prevalence of cases for all causes. Conclusion: women had higher mortality from non-communicable diseases, and men from suicide and interpersonal violence. These results were consistent across decades. A high likelihood of multicomorbidity was evident for all causes.